Measuring the long-run effect of economic growth, population aging, and unemployment on carbon emissions in South Asia - Musarat Abbas; Ling Yang (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
During the last two decades, South Asia has faced extreme climate change events of heatwaves, floods, storms, droughts, and fires, affecting economies and millions of people. Meantime, the region has also experienced a notable change in economic growth, population aging, and unemployment rate. However, the carbon implications of these factors are still limited, and it requires further exploration to understand their association with carbon emissions for environmental sustainability. Thus, the prime aim of this study is to empirically evaluate the effect of economic growth, population aging, and unemployment on carbon emissions in South Asia by controlling trade and renewable energy. For this, panel data from 1996 to 2020 for Bangladesh, India, Nepal, Pakistan, and Sri Lanka have been used for empirical analysis. The study employs fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) estimation techniques using Stata and EViews software. Economic growth, population aging, and trade openness increase carbon emissions while unemployment and renewable energy reduce them. This study also confirms an inverted U-shaped association between income and carbon emissions in South Asia.
Keywords: 330; CO2 emissions; aging; unemployment; trade openness; renewable energy; South Asia